An Evolutionary Fuzzy Hybrid System for Educational Purposes - Esmin, Ahmed Ali Abadalla; Carvalho, Marcos Alberto de; Moraes, Carlos Henrique Valério de; Lambert-Torres, Germano (IntechOpen, 2012)
None